2003
DOI: 10.1046/j.1365-2567.2003.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of macrophage inflammatory protein‐1α on protective immunity mediated by antiviral cytotoxic T cells

Abstract: SUMMARYMacrophage in¯ammatory protein 1a (MIP-1a), a member of the CC-chemokine subfamily, is known to induce chemotaxis of a variety of cell types in vivo. Although the role of MIP-1a in in¯ammatory responses generated following primary infection of mice with many different pathogens has been characterized, the in¯uence of this chemokine on the generation of antigen-speci®c T-cell responses in vivo is less well understood. This is important, as virus-speci®c CD8T lymphocytes (CTL) play a crucial role in defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…2C). The numbers of NP68-specific CD8 T cells detectable during primary infection were lower than those reported using HKx31 strain of influenza, particularly in the lungs (23), although the total number of CD8 T cells and the frequency of NP68 tetramer binding CD8 cells were similar to those previously reported by us for H17 (19,20) and for the HKx31 strain (24). To increase the yield of memory CD8 T cells from solid organs we employed collagenase digestion before cell isolation.…”
Section: Cd62l High Memory Cd8 T Cells Distribute Normally To Nonlympsupporting
confidence: 67%
See 2 more Smart Citations
“…2C). The numbers of NP68-specific CD8 T cells detectable during primary infection were lower than those reported using HKx31 strain of influenza, particularly in the lungs (23), although the total number of CD8 T cells and the frequency of NP68 tetramer binding CD8 cells were similar to those previously reported by us for H17 (19,20) and for the HKx31 strain (24). To increase the yield of memory CD8 T cells from solid organs we employed collagenase digestion before cell isolation.…”
Section: Cd62l High Memory Cd8 T Cells Distribute Normally To Nonlympsupporting
confidence: 67%
“…with 5 ϫ 10 6 PFU. Ovaries were removed 5 or 8 days later, and a single ovary from each mouse analyzed for rVV titers, as described previously (19). The remaining ovaries, as well as OdLN and spleen were harvested for immunostaining and in vitro CTL assays.…”
Section: Viruses and Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that chemokines play a critical role in the development of innate as well as acquired immunity against a variety of viruses, bacteria, fungi, and parasites [9][10][11]. The protective role of chemokines has been attributed to their ability to activate leukocytes and facilitate their recruitment to the site of infection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…5B, 5C) (38)(39)(40). Moreover, CCL3 has been shown to have adjuvant effects on CD8 + T cell priming, to increase CD8 + T cell effector functions, and to be involved (together with other chemokines) in recruiting CD8 + T cells to inflamed sites (39,(41)(42)(43). Although CCL3 and CCL4 both bind to CCR5, the former, but not the latter, also binds to CCR1, which may account for their diverging biological effects (36,39).…”
mentioning
confidence: 99%